Optimization of Clove Oil Blending Ratio to Gasoline Engine Performance - Nasruddin A. Abdullah; Bagas Prayoga; Fazri Amir; Teuku Azuar Rizal; Muhammad Amin; Hamdani Umar (UIN Sumatera Utara, 2025)
The increasing need for cleaner and more efficient fuels encourages the use of bio-additives to improve the combustion quality of gasoline engines. However, research on the direct effect of variations in the ratio of clove oil in Pertalite gasoline on engine performance and emissions is still limited. This study examined the effect of mixing clove oil in four fuel compositions, namely pure Pertalite (P0), Pertalite + clove oil 0.5% (P0.5), 1% (P1), and 2% (P2), on engine performance parameters and exhaust emission characteristics. The results showed that the P2 blend provided the most significant improvement in engine performance, characterized by a 4.6% increase in torque and 6.3% power, a decrease in specific fuel consumption of up to 7.1%, and an increase in calorific value of up to 7.8%. Thermal efficiency also increased at high rounds of 1 %, indicating better energy conversion. In terms of emissions, a decrease in CO of 0.006% and a decrease in CO₂ of 0.1% indicate more complete combustion, although HC increases by 34 ppm (parts per million) due to the volatile characteristics of clove oil. Overall, the addition of 2% clove oil has been shown to improve combustion quality without engine modification. These findings confirm the potential of clove oil as a viable and relevant renewable bio-additive to support energy transition efforts towards a cleaner and more sustainable transportation system.